Exploring Gender Constructs in Media Narratives - Elharraki, Badia (Journal of Pragmatics and Discourse Research, 2024)
This paper seeks to examine the discourse of women who have experienced marital violence as depicted in Moroccan media. Specifically, we will investigate how these women justify their discourse through authorization, aiming to construct arguments that portray them as victims and vilify their abusive husbands. Our analysis focuses on content from Medi 1TV, particularly the talk show "Qesset Nnass" (the story of people), where women articulate their viewpoints through authorization, conveying messages that require contextual understanding for interpretation. Our research is guided by the premise that the interaction between media and audience is intricate and significant, serving as a platform for women to validate their experiences while challenging the actions of their abusers, and providing Moroccans with an avenue to express their perspectives on these issues. Consequently, we aim to assess the effectiveness of these women's persuasive efforts within the show. Given the nature of our topic, our research employs a combination of methodologies. While we utilize a qualitative approach to analyze the discourse of the women subjected to violence through direct observation, we also employ a quantitative method to examine audience comments. This methodological approach enables us to explore the relationship between media content and public opinion, shedding light on the extent of its mutual and direct influence.